Overt and Covert Effects of Endogenous and Exogenous Ecdysone in Puparium Formation of Flies - Zdarek, Jan (1970)
Mature larvae of Sarcophaga argyrostoma fail to form puparia when kept in contact with water, but pupariate after having been subsequently exposed to dryness for 30 hr. They become increasingly more sensitive to injected ecdysone the longer the exposure to dry conditions. A second wet treatment halts the production of hormone that had occurred during the dry period, and reduces a sensitization to injected ecdysone during the intervening dry treatment. Apparently, injected ecdysone had cumulative effects not with the endogenous or exogenous hormone, but with its covert effects which had arisen during the dry period and persisted throughout the second wet period. The hind parts of larvae ligated at the end of a wet period pupariate when injected with either one massive dose of ecdysone, or a far smaller total of several subsequent doses. In the case of two unequal doses, the effect was greater when the smaller dose was injected first. In order to get pupariation with minimal effective doses, a continuous supply of the hormone during a certain period is required. It is suggested that the inhibition of pupariation by moisture has arisen as an adaptation to unfavorable conditions.